Investigating EFL Students’ Active-to-Passive Voice Errors through the Lens of the Surface Strategy Taxonomy - Sakhi Murad Ghorianfar; Asadullah Faizy; Nesar Ahmad Wahedi (Asosiasi Dosen Perguruan Tinggi Islam, 2026)
EFL learners often find grammar challenging, particularly when using the passive voice, which often leads to errors. This study investigated the types of errors that EFL students made when converting active into passive constructions, using the Surface Strategy Taxonomy (SST) proposed by Dulay et al. (1982) as the analytical framework. A quantitative research design was employed, and data were collected through a test administered to 50 English majors in the English Language and Literature Department at Ghor University. The test consisted of 21 active sentences in various tenses, which students were required to transform into passive sentences. Analysis of the results revealed four main types of errors according to the SST model. Misformation errors were the most frequent (46.10%), followed by omission errors (34.58%). Addition errors were less common (10.85%), while misordering errors occurred the least (8.47%). The findings provide educators with valuable insights, helping them refine teaching strategies and improve students’ proficiency in the passive voice.